Grip strength is a representative measure of muscle weakness in the upper extremity after stroke. Issue 6 (17th August 2016) - Ekstrand, Elisabeth; Lexell, Jan; Brogårdh, Christina
Abstract : Background: Muscle weakness is the most common impairment in the upper extremity after stroke, leading to a reduced ability to use the arm and the hand in daily activities. Grip strength is easier to measure than precise, but more time-consuming, isokinetic and isometric arm muscle strength measurements. It would therefore be advantageous in a clinical setting if grip strength could be used as a proxy for muscle strength in the entire upper extremity. Objective: To investigate the association between grip strength and isometric and isokinetic arm muscle strength in persons with chronic stroke. Methods: Forty-five persons with mild-to-moderate paresis in the upper extremity, at least 6 months post-stroke participated. Isometric grip strength was measured with a computerized grip dynamometer and arm strength (isometric shoulder abduction and elbow flexion as well as isokinetic elbow extension and flexion) with an isokinetic dynamometer. Pearson's correlation coefficient was used to determine the association between the muscle strength measurements. Results: There were significant correlations ( p  < .0001) between grip strength and all arm strength measurements in both the more affected ( r  = 0.77–0.82) and the less affected upper extremity ( r  = 0.65–0.82). Conclusion: This cross-sectional study showed that grip strength is strongly associated with muscle strength in the arm in persons in the chronic phase after stroke. As grip strength is easy to measure and less time-consuming than arm muscle strength measurements, this implies that grip strength can be a representative measure of muscle weakness of the entire upper extremity in the chronic phase after stroke.